Pengenalan Pembuatan Sabun Cuci Piring Sebagai Usaha Baru Ibu-Ibu Kepling V Kelurahan Tanah Seribu - Milda Zohra; Sri Damayani; Siti Hotma Sari Pulungan; Dhea Tri Fadillah; Tanti Jumaisyaroh Siregar (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
A community service project has been implemented in Kepling V, Tanah Seribu District, with the aim of increasing women's understanding of entrepreneurship. One such project involved the introduction of dishwashing soap made using off-the-shelf components. The aim of this community service project is to present dishwashing soap making as a potential business venture. Purchasing equipment and supplies, making dish soap, collaborating with the Head of Environment V of Tanah Seribu Village, counseling and evaluation were the research procedures carried out. The mothers who took part in this exercise expressed their interest in launching a company that produces dishwashing soap.